The Actualization of Adopted Children’s Inheritance Rights: A Multidisciplinary Legal Study in West Jempong, Mataram City - Rendra Khaldun (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2025)
Adoption is widely practiced in Indonesia, particularly among married couples who have not been blessed with biological children. The primary purpose of adoption is often to continue family lineage when a couple is unable to have children biologically. However, in certain regions, such as Lombok, adoption may also serve additional social and cultural purposes, including fulfilling traditional expectations related to having descendants. In many cases, adoption becomes a humane and socially accepted solution for couples who have long desired the presence of a child in their family. This study aims to analyze the legal position and inheritance rights of adopted children within the local community of West Jempong, Mataram City. The research employs a descriptive qualitative method by combining a literature review with field observations to ensure the validity of the findings. The results indicate that although adopted children are socially recognized within the family structure, their inheritance rights are influenced by the applicable legal system, including civil law principles and local practices. In inheritance law, the heir as the owner of the property has the authority to determine the distribution of his or her assets. Nevertheless, the concept of the absolute share (legitieme portie) ensures that certain heirs in the direct line are legally entitled to a minimum portion of the inheritance. This study highlights the interaction between legal norms, social practices, and the position of adopted children in inheritance arrangements within the community.